Speech and Gesture Complementarity in a Preschooler's Conceptualization of Mechanical Equilibrium - Maria-Eleni Chachlioutaki; Panagiotis Pantidos (MDPI AG, 2024)
Considering learning to be situated and modally defined, the purpose of this paper was to identify and describe action structures as thought structures. We aimed to investigate the modal patterns that emerge during the learning process through a case study that examines how a 5-year-old preschool child conceptualizes the dimensions of mechanical equilibrium. Three identical tests were designed to elicit different modal responses from the student. These tests consisted of three tasks that differed semiotically from one another. The tests were conducted at different time points and were interspersed with two contextually distinct teaching interventions. The findings demonstrate that, while conceptualizing mechanical equilibrium, the student constructed meanings through semantic supplements of speech, bodily expression, and drawing, thus creating a form of multimodal syntax to express their thoughts. Complementarity evidently contributes to the concept of variability and serves as components of learning, which is perceived as a dynamic process.